Excitation funetions and isomerie ratios for the isomeric pair 106mAg/I06gAg in the 107Ag(d,t) reaction - Lalli, M. E.; Wasilevsky de Lammirato, Catalina; Herreros Husher, O. R.; Jorge Nassiff, Sonia (1976)
Fil: Lalli, M. E. Comisión Nacional de Energía Atómica; Argentina